Rare bird documentation form for Lesser Black-backed Gull at Manhattan Point at West Okoboji Lake, 1999 - Kenne, Matthew C.et al (1999)
Rare bird documentation form for a Lesser Black-backed Gull at Manhattan Point at West Okoboji Lake in Dickinson County, IA on November 21, 1999. Epson - sheet feed